Analysis of Outcome Indicators of Cancer-Related Fatigue Treated with Chinese Herbal Compounding - Li ZH; Zhang XW; Weng YY; Zhou L; Wang F (International Journal of General Medicine, 2022)
Zhong-Hui Li, Xin-Wei Zhang, Yue-Yan Weng, Lei Zhou, Fang Wang Department of Oncology, Wangjing Hospital, China Academy of Chinese Medical Sciences, Beijing, People’s Republic of ChinaCorrespondence: Fang Wang, Department of Oncology, Wangjing Hospital, China Academy of Chinese Medical Sciences, Huajiadi Road, Beijing, 100102, People’s Republic of China, Email wf074500@163.comObjective: In the direction of evaluating the current status of outcome indicators and control group selection in randomized controlled studies of Chinese herbal compounding (such as Sini plus Renshen Decoction, Jianpifuzhengfang, Bufei Jianzhong Decoction, etc) for cancer-caused fatigue and to provide a reference for clinical studies of Chinese herbal compounding for cancer-caused fatigue.Methods: Randomized controlled studies of Chinese herbal medicine for cancer-caused fatigue in the midst of 2012 and 2022 were searched in CNKI, PubMed, and EMBASE databases on the China Knowledge Network, and the literature was screened using NoteExpress. Two researchers independently conducted the literature review, and then the studies that met the criteria were grouped and analyzed adopting qualitative analysis of outcome indicators and control groups.Results: A total of 70 randomized controlled studies that met the requirements were included, and after doing statistical analysis, it can draw to the conclusion that the risk of bias in the included studies was high; at the same time, the TCM evidence score scale, objective indicators, and safety indicators were underutilized; additionally, there were no uniform standards for the fatigue scale, and the selection of control groups lacked balance and consistency.Conclusion: The outcome indicators of TCM compound treatment of cancer-caused fatigue should be on the basis of the principle of “diagnosis and treatment” in TCM, the proportion of objective indicators should be exaggerated, as well as the interventions in the control group should be unified.Keywords: Chinese herbal compound, cancer-related fatigue, randomized controlled trial, outcome indicators, control group